Emerging positive education intervention for clean sport behavior - Abdullah, Haslinda (2024)
Doping damages athletes’ physical health and sports integrity, replacing fair competition with a false feeling of strength. Besides, young athletes are more prone to harmful behaviors when they do not have a solid ethical basis to guide them.